2023
DOI: 10.1002/ente.202201521
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nitride from Ammonia Borane and Alkali Amidoboranes and Its Features for Carbon Dioxide Capture

Abstract: Herein, three boranes are studied as potential precursors of boron nitride (BN) and their carbon dioxide adsorption capacity is evaluated. The selected boranes are ammonia borane (AB, NH3BH3), lithium amidoborane (LiAB, LiNH2BH3), and sodium amidoborane (NaAB, NaNH2BH3), and they are pyrolyzed at four different temperatures. All the characterization techniques show the formation of BN from the three boranes. However, LiAB and NaAB form hexagonal BN (h‐BN) at a lower temperature in comparison with AB. The inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…AB@ZIF-8 underwent pyrolysis in a Vectar Ltd VTF7 tubular furnace at 800 °C, a temperature choice based on a previous study which revealed that bulk BN obtained from AB could adsorb CO 2 when pyrolyzed between 600 and 800 °C. 23…”
Section: Methodsmentioning
confidence: 99%
“…AB@ZIF-8 underwent pyrolysis in a Vectar Ltd VTF7 tubular furnace at 800 °C, a temperature choice based on a previous study which revealed that bulk BN obtained from AB could adsorb CO 2 when pyrolyzed between 600 and 800 °C. 23…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, many steps are needed to synthesize porous BN materials with a good composition, structure and porosity (such as hard templating methods or polymer-derived ceramic routes) [18,19]. Moreover, we suspect that defects within the BN structure and/or carbon-doping would be needed to improve gas sorption [9]. In the present work, a porous carbon-doped BN is synthesized in order to enhance its CO 2 adsorption performance.…”
Section: Introductionmentioning
confidence: 99%
“…BN can indeed be used in applications within corrosive environments where the widely investigated oxide ceramics cannot work properly. Boron nitride (BN) is a non-oxide ceramic with a very wide range of applications, such as for energy or medicine [7][8][9]. It can be synthesized from numerous molecular precursors, and notably, from ammonia borane (AB) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation